Ethnobotany of tree ferns in Pasir Menyan Hamlet, Sukamandi Village, Subang, West Java, Indonesia - SURYANA SURYANA; JOHAN ISKANDAR; PARIKESIT PARIKESIT; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
Suryana, Iskandar J, Parikesit, Partasasmita R. 2018. Ethnobotany of tree ferns in Pasir Menyan Hamlet, Sukamandi Village, Subang, West Java, Indonesia. Biodiversitas 19: 2044-2051. Tree ferns are plants that grow mostly in the highlands, such as in the forest area of ??Tangkuban Perahu Mountain, Subang, West Java, Indonesia. The existence of tree ferns and their population are threatened, along with forest damage and over-exploitation. The present study was directed to examine the local knowledge of the community around the forest area of ??Mount Tangkuban Perahu in term of local names, utilization, suitability to grow, and conservation efforts of tree fern. This research was conducted in Pasir Menyan Hamlet, Sukamandi Village, Subang, West Java in March-June 2017. The method used in this study was mixed-method, a combination of qualitative and quantitative, while some field techniques, including observation, semi-structured interviews, structured interviews, and botanical survey of tree ferns were carried out. The results of the study showed that it was recorded 8 landraces of tree fern were recognized by informants, namely pakis tihang, pakis sieur, bagedor, pakis minyak, pakis payung, pakis cempor, pakis bulu, and sijabrig. In terms of local knowledge on tree ferns, people with ages 50-59 years old recorded a right a higher percentage of tree ferns than the children and younger people. Regarding education, the result showed that a low level of education had the highest level of knowledge of local names and utilization of tree ferns as vegetables, ornamental plants, growing media, and for handicrafts because of they still intensive interaction with forest ecosystem and tree ferns. On the basis conservation of tree ferns, the rural people of Sundanese people have a tradition to prohibit (pamali) to cut forest on the river bank, open slopes, closed forests, damaged forest areas, and in the valleys. In addition, traditional conservation practice on tree ferns has recorded, for example, rural people of Pasir Menyan Hamlets have traditional prohibited to open sacred forest, including to take of tree ferns.